Determining Relation between Gallstone and Lipid Profile - Singh, Rabin Raj; Adhikari, Sunil Chandra; Bastakoti, Ravi; Regmi, Sunil; Baskota, Ravindra; Giri, Kshitij (Birat Journal of Health Sciences, 2018)
Introduction: Cholelithiasis is presence of stone in gallbladder. Female sex, obesity, pregnancy, fatty foods, all are associated with an increased risk of developing gallstones. There is paucity of information regarding relation of cholelithiasis and lipid profile. In this study the association of serum lipids to cholelithiasis has been tried to been elucidated. Objectives: The general objective was to determine the relation of Serum lipid in cholelithiasis. The specific objectives were to compare the relation between serum cholesterol, serum triglyceride, serum HDL and serum LDL in patients with and without gallstones. Methodology: A prospective, observational, hospital based study was conducted at Koshi Zonal Hospital from March 2017 to February 2018. Fifty four patients having gallstone (Group A) were compared with equal number of patients without gallstone (Group B). Data was entered into SPSS/MS Excel. Statistical Analysis was done by using Chi-square test. A 95% confidence interval was taken, and P value less than 0.05 was considered as statistically significant. Results: In Group A, 61%(33) patients were of age less than 45 years and 91%(49) were female. In group A, 3.7 %(2) and in group B, 7.4%(4) had raised serum cholesterol. Greater number of patient in group A had raised serum triglyclyceride and LDL as compared to group B. 18.5%(10) of group A had low serum HDL, and 9.3% (5) of group B had low serum HDL. Except for finding of gallstone more common in female, other findings had no statistical significance. Conclusion: There exists an inverse correlation between Serum Cholesterol and serum HDL with gallstone and positive association between serum Triglyceride and serum LDL with cholelithiasis. However the association could not reach the statistical significance. BJHS 2018;3(2)6:418-422.